1995
DOI: 10.1159/000201261
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Mucosal Glycoprotein Synthesis in Inflammatory Bowel Is Not Related to Cigarette Smoking

Abstract: Patients with ulcerative colitis are usually non- or ex-smokers in contrast to Crohn’s disease where smoking is common. Abnormalities of quantity and quality of intestinal mucus have been postulated in the pathogenesis of these diseases. It is possible that smoking habit may exert its effects via changes in mucus in inflammatory bowel disease. We have therefore studied incorporation of N-acetylglucosamine into synthesized colonic mucin in explants from 85 controls with normal colonoscopic appearances and histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…The thickness of mucus layer is determined by the dynamic equilibrium between secretion of mucins and its removal into the lumen [44]. For mild and moderate UC, the synthesis of secretory mucins in UC was controversially reported, showing all directions -no change [45,46], increase [47] or decrease [48] -in the cultures of tissue biopsies when compared to healthy controls. However, the thickness of the adherent mucus gel was found generally lower or unchanged [44,49], possibly due to excessive removal.…”
Section: Discussionmentioning
confidence: 99%
“…The thickness of mucus layer is determined by the dynamic equilibrium between secretion of mucins and its removal into the lumen [44]. For mild and moderate UC, the synthesis of secretory mucins in UC was controversially reported, showing all directions -no change [45,46], increase [47] or decrease [48] -in the cultures of tissue biopsies when compared to healthy controls. However, the thickness of the adherent mucus gel was found generally lower or unchanged [44,49], possibly due to excessive removal.…”
Section: Discussionmentioning
confidence: 99%
“…Mucus synthesis has been shown to be normal in non-inflamed colonic mucosal explants from UC patients but is likely to be reduced in active colitis [32]. An alternative explanation for the striking lack of the mucus layer in active colitis could be increased enzymatic breakdown of the secreted mucus.…”
Section: Alterations In the Mucosal Barrier In Inflammatory Bowel Dismentioning
confidence: 99%
“…It has been speculated that some of the protective effect of smoking may be related to nicotine, and nicotine patches have been used, with some benefit, to treat UC [25,261. Previous work has suggested that mucosal biopsies from smokers with UC have higher rates of mucin synthesis when cultured in uitro than biopsies from non-smokers [27], although studies on mucosal biopsies in uitro from smoking and non-smoking control subjects have failed to show any such effect [28]. Furthermore, nicotine infusions in rabbits have an unusual effect on mucus thickness in the colon; causing a reduction in the thickness at very low concentrations, and an increase at higher concentrations [29].…”
Section: Disc U Sslo Nmentioning
confidence: 99%